(untitled) (Comprehensive Journal of Science, 2025)
This This study aims to investigate the evolution of ethical leadership theory and analyze its theoretical and practical dimensions. The study demonstrates that international factors, such as conflicts and the spread of corruption, have heightened interest in ethical leadership. The theoretical framework is based on social learning theory and social exchange theory, highlighting the reciprocal relationship between the leader and subordinates. The findings reveal two main dimensions of ethical leadership: the moral person and the moral manager, identifying ten key traits that characterize an ethical leader. The study also demonstrates the positive impact of ethical leadership on organizational performance, ethical culture, employee satisfaction, and organizational justice.